Cross‐linking analysis reveals the putative dimer structure of the cyanobacterial BLUF photoreceptor PixD. Issue 15 (14th May 2015) - Ren, Shukun; Sugimoto, Yuki; Kobayashi, Taichi; Masuda, Shinji
Abstract : PixD is a blue light using flavin (BLUF)‐type blue‐light photoreceptor controlling phototaxis in the cyanobacterium Synechocystis sp. PCC6803. The crystal structure of PixD shows a decamer, although in solution an equilibrium is maintained between the dimer and decamer. Because the ratio of these two conformers is altered by illumination, the equilibrium state determines photosensitivity. However, no structural information is available for the PixD dimer. Here, we report a predicted structure for the dimer based on docking simulation, mutagenesis, and mass spectrometry‐based cross‐linking analyses. The results indicate the importance of the PixD C‐terminus for dimer preference and photosensitivity. Abstract : We performed docking simulation and MS‐based cross‐linking analysis of PixD. A putative dimer structure of PixD is revealed. The dimer structure of PixD suggests the importance of its C‐terminus for the dimer formation.